2009
DOI: 10.1590/s1517-83822009000400003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of branched-chain amino acids, valine, isoleucine and leucine on the biosythesis of bitespiramycin 4"-O-acylspiramycins

Abstract: Bitespiramycin, a group of 4"-O-acylated spiramycins with 4"-O-isovalerylspiramycins as the major components, was produced by recombinant spiramycin-producing strain Streptomyces spiramyceticus harboring a 4"-O-acyltransferase gene. The experiment was initially performed in synthetic medium with 0.5 g l-1 Valine, Isoleucine or Leucine feeding at 36 h cultivation. When valine was fed, the biological titer of bitespiramycin was 45.3% higher than that of the control group, but the relative content of total isoval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Phosphoserine, an intermediate in serine and cysteine biosynthesis, branched amino acids such as threonine and isoleucine, which also aid in the fermentation process, were piled up. 47 Further, we found a significant accumulation of methionine and sulfate ions, a marker for amino acid sufficiency. 48 This explained the prolongation of the logarithmic phase of transgenic strains, probably via inhibition of autophagy signaling.…”
Section: ■ Results and Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Phosphoserine, an intermediate in serine and cysteine biosynthesis, branched amino acids such as threonine and isoleucine, which also aid in the fermentation process, were piled up. 47 Further, we found a significant accumulation of methionine and sulfate ions, a marker for amino acid sufficiency. 48 This explained the prolongation of the logarithmic phase of transgenic strains, probably via inhibition of autophagy signaling.…”
Section: ■ Results and Discussionmentioning
confidence: 65%
“…Glycine, the starting ingredient of thiamine and other amino acids, seemed to be exhausted. Phosphoserine, an intermediate in serine and cysteine biosynthesis, branched amino acids such as threonine and isoleucine, which also aid in the fermentation process, were piled up . Further, we found a significant accumulation of methionine and sulfate ions, a marker for amino acid sufficiency .…”
Section: Resultsmentioning
confidence: 72%
“…Our study also revealed the effect of branched‐chain amino acids on the morphology of O. ulmi (Table 2), possibly associated with their acting as precursors for fusel alcohols, fusel acids or other similar secondary metabolites. Furthermore, some amino acids such as valine (Val), isoleucine (Ile) or leucine (Leu) are precursors for other secondary metabolites (Li et al. 2009).…”
Section: Discussionmentioning
confidence: 99%